New process for production of fermented black table olives using selected autochthonous microbial resources - Tufariello, Maria; Durante, Miriana; Ramires, Francesca A.; Grieco, Francesco; Tommasi, Luca; Perbellini, Ezio; Falco, Vittorio; Tasioula-Margari, Maria; Logrieco, Antonio F.; Mita, Giovanni; Bleve, Gianluca (Frontiers in Microbiology, 2015)
Table olives represent one important fermented product in Europe and, in the world, their demand is constantly increasing. At the present time, no systems are available to control black table olives spontaneous fermentation by the Greek method. During this study, a new protocol for the production of black table olives belonging to two Italian (Cellina di Nardò and Leccino) and two Greek (Kalamàta and Conservolea) cultivars has been developed: for each table olive cultivar, starter-driven fermentations were performed inoculating, firstly, one selected autochthonous yeast starter and, subsequently, one selected autochthonous LAB starter. All starters formulation were able to dominate fermentation process. The olive fermentation was monitored using specific chemical descriptors able to identify a first stage (30 days) mainly characterized by aldehydes; a second period (60 days) mainly characterized by higher alcohols, styrene and terpenes; a third fermentation stage represented by acetate esters, esters and acids. A significant decrease of fermentation time (from 8-12 months to a maximum of 3 months) and an significant improvement in organoleptic characteristics of the final product were obtained. This study, for the first time, describes the employment of selected autochthonous microbial resources optimized to mimic the microbial evolution already recorded during spontaneous fermentations.